Disentangling attentional deficits in psychopathy using visual search: Failures in the use of contextual information. (November 2015) - Hoppenbrouwers, Sylco S.; Van der Stigchel, Stefan; Slotboom, Jantine; Dalmaijer, Edwin S.; Theeuwes, Jan
Abstract: Psychopathic patients show a lack of affective reactivity in threatening situations. Previous research has shown that this lack of affective reactivity can be explained by diminished processing of goal-irrelevant information once psychopathic individuals initiate goal-directed behavior. Although the response modulation theory of psychopathy has claimed that this is caused by deficits in top-down–bottom-up integration of information, it is currently unclear whether it is predominantly bottom-up or top-down attention that is affected. To investigate which aspect of attention is causing these deficits, we administered three visual search tasks in which top-down attention was required to find the target (i.e., search for a specific feature) in the presence or absence of bottom-up and top-down cues. The research group consisted of 30 violent offenders, with varying degrees of psychopathy. Dimensional analyses showed no relationship between psychopathy and deficits in processing bottom-up cues but a strong correlation with deficits in processing top-down cues and core psychopathic personality traits. The current study corroborates the notion that psychopathic traits are associated with response modulation problems, and adds that this is predominantly related to deficits in top-down incorporation of contextual information. Interestingly, this failure of top-down incorporation was observed even when top-down cues were beneficial for current goals. Highlights: Psychopathy is characterized by behavioral rigidity. The response modulation theory postulates this which can be explained by attention. We used three visual search experiments to test attention in psychopathy. Bottom-up attention appears normal in psychopathy, while top-down attention is affected. This makes it difficult for psychopathic individuals to incorporate contextual information.